2020
DOI: 10.1111/gwat.13050
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Plans in the United States: Regulatory Frameworks and Management Goals

Abstract: Groundwater management plans are an important tool for preventing and addressing degradation and depletion of the resource. Through plans, water users and regulators set forth goals and identify strategies to address the needs of multiple resource users while considering physical constraints of the groundwater resource. This research examines the status of groundwater management plans in the United States, identifying in which states groundwater management plans are produced and the circumstances that lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Despite these examples, effective conjunctive management of surface water and groundwater is lagging behind scientific understanding in many settings. A review of 54 groundwater management plans in the U.S. found that only six (11%) had quantitative targets related to streamflow depletion (Gage and Milman 2020), and there are many regions around the world where streamflow depletion is not addressed by water management. In India, for example, groundwater and surface water are typically managed separately (Srinivasan and Kulkarni 2014;Harsha 2016), and therefore "groundwater use is not considered to be linked to streamflow and is decoupled from the surface water allocation" by water management groups (Biggs et al 2007).…”
Section: Management and Policy Of Interconnected Groundwater And Surf...mentioning
confidence: 99%
“…Despite these examples, effective conjunctive management of surface water and groundwater is lagging behind scientific understanding in many settings. A review of 54 groundwater management plans in the U.S. found that only six (11%) had quantitative targets related to streamflow depletion (Gage and Milman 2020), and there are many regions around the world where streamflow depletion is not addressed by water management. In India, for example, groundwater and surface water are typically managed separately (Srinivasan and Kulkarni 2014;Harsha 2016), and therefore "groundwater use is not considered to be linked to streamflow and is decoupled from the surface water allocation" by water management groups (Biggs et al 2007).…”
Section: Management and Policy Of Interconnected Groundwater And Surf...mentioning
confidence: 99%
“…Infrastructurebased initiatives also occur, such as relocating boreholes away from sensitive GDEs (e.g., Beauce Aquifer, France; Verley 2020) and piping free-flowing artesian bores (e.g., Great Artesian basin, Australia; New South Wales Government 2016Government , 2019. Commentators also tend to recommend rules and management plans to protect GDEs, including modeling, thresholds for avoiding adverse impacts, triggers for action, large-scale monitoring, and good stakeholder engagement (Noorduijn et al 2019, Elshall et al 2020, Thomann et al 2020, Gage and Milman 2021, Saito et al 2021.…”
Section: Environmental Rules and Environmental Rights For Groundwater...mentioning
confidence: 99%
“…These political and legal obstacles, as well as the rigidity of existing water and administrative law regimes, may pose "serious impediments that generally prevent governmental water agencies from engaging in scientifically valid adaptive management" of groundwater, including as to ecological protections (Craig 2020:11). In jurisdictions that require stakeholder consensus to institute legal management plans or other rules, progressive, quantified protections may simply never eventuate (Gage and Milman 2021). In practice, groundwater plans tend to adopt an ad hoc rather than a structured approach to adaptive learning (Thomann et al 2020).…”
Section: Environmental Rules and Environmental Rights For Groundwater...mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these examples, effective conjunctive management of surface water and groundwater is lagging behind scientific understanding in many settings. A review of 54 groundwater management plans in the United States found that only six (11%) had quantitative targets related to streamflow depletion (Gage and Milman, 2020), and there are many regions around the world where streamflow depletion is not addressed by water management. For example, in India groundwater and surface water are typically managed separately (Srinivasan and Kulkarni, 2014;Harsha, 2016), and therefore "groundwater use is not considered to be linked to streamflow and is decoupled from the surface water allocation" by water management groups (Biggs et al, 2007).…”
Section: Management and Policy Of Interconnected Groundwater And Surface Watermentioning
confidence: 99%